UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BATANG MANGGA KWENI (Mangifera odorata Griff) TERHADAP Escherichia coli ATCC 25922 DAN Staphylococcus aureus ATCC 25923 - Wuri Prihatiningtiyas; Yeni Mariani; H A Oramahi; Fathul Yusro; Lolyta Sisilia (Universitas Tanjungpura, 2018)
The aims of this research are to determine the secondary metabolite content found in the ethanol extract of kweni mango bark (Mangifera odorata Griff) and analyze its potency as a natural antibacterial against Escherichia coli and Staphylococcus aureus. The research was started by maceration process using 96% ethanol solvent, then evaporated at 40-50oC and obtain yield of 20,61% with powder content of 8,34%. Furthermore, phytochemical screening was performed qualitatively to determine the secondary metabolite of the extract. The results showed that ethanol extract of M. odorata Griff bark contained secondary metabolites such as alkaloids, flavonoids, saponins, tannins, terpenoids and phenolics. In this study antibacterial activity was carried out using disc diffusion method in Plate Count Agar media and incubated for 24-48 hours. The results showed that the largest diameter of inhibitory zones formed at a concentration of 15 mg/ml for S. aureus was 12,33 mm with strong classified and for E. coli bacteria with a concentration of 200 mg/ml of 23,67 mm with very strong classified, and almost equal with the result shown by 30 µg tetracycline as positive control, which is 25 mm. The results of this study it can be concluded that the ethanol extract of the kweni mango bark (M. odorata Griff) is bacteriostatic.Keywords: antibacterial activity, Mangifera odorata Griff, phytochemical screening, Escherichia coli, Staphylococcus aureus.